Inhibitory concentrations of gambier (Uncaria gambir Roxb.) catechins extract against Streptococcus mutans - Inmawaty, Jesieca; Sudjarwo, Indrati; Satari, Mieke Hemiawati (Padjadjaran Journal of Dentistry, 2012)
Introduction: Catechin which extracted from gambir (Uncaria gambir  Roxb) is a major component of polyphenol compounds. The catechins compound acts as an antibacterial. The study was to analyze the inhibitory concentration gambir catechin extract against Streptococcus mutans as the bacteria that play a role in the formation of dental caries. Methods: The study was conducted in a laboratory experiment by testing inhibitory concentration gambir catechin extract, through Kirby Bauer disk diffusion method on plates TYCSB for 1 x 24 hours. Test bacteria Streptococcus mutans isolated from saliva. The used suspension of bacteria was made according to the standard turbidity of Mc Farland 0.5 are each 1 ml suspension containing 1.5 x 108 bacteria. The powder obtained from catechin gambir extract through freezing method. Results: Catechins concentrations of 20% produces the lowest inhibition, with an inhibitory diameter of 0,615 cm. The largest inhibition produces by the concentration of catechins with 80% inhibition at 1,085 cm inhibitory diameter. Conclusion: The higher concentration of catechins, the greater inhibition produces. Conversely, the lower concentration of catechins will be lower inhibition produces. the resulting zone of inhibition will be smaller.